Corneal Ulcer in Dogs and Cats: Novel Clinical Application of Regenerative Therapy Using Subconjunctival Injection of Autologous Platelet-Rich Plasma - Farghali, Haithem A.; AbdElKader, Naglaa A.; AbuBakr, Huda O.; Ramadan, Eman S.; Khattab, Marwa S.; Salem, Noha Y.; Emam, Ibrahim A. (Frontiers in Veterinary Science, 2021)
Background: Corneal ulcer could be a major source of distress in small animals with many contributing agents. In recent years, few studies evaluated the efficacy of platelet-rich-plasma (PRP) in healing corneal ulcers. Aim: This study aimed to assess the ability of subconjunctival injection of autologous PRP in the treatment of corneal ulcers in dogs and cats as well as estimate expression of MMP-2 and 9 and oxidative stress biomarkers in these patients. Methods: A total number of 28 animals (16 cats and 12 dogs) were enrolled in this study. Each animal subjected to clinical, neurologic, and ophthalmic examinations where the type of ulcer was documented. Blood and tear samples were collected for evaluation of oxidative biomarkers and MMPs, conjunctival swabs were taken to identify the involved organism. PRP was prepared from each animal and given as a subconjunctival injection, the number of injections was done according to case response. Clinical follow up was done and documented for each case. Results: in cat patients, female and Persian cats were most affected, unilateral, and superficial ulcers were most recorded. In dogs, males, unilateral, and superficial ulcers were most recorded. FHV-1 was most identified in cats while Staph. Was most identified in dogs. The number of injections needed to achieve healing was recorded, with 50% of dogs needing two injections with one-week intervals and 50% of cats needed three injections with a one-week interval. Alterations in both oxidative biomarkers and MMPs were recorded in affected animals. Conclusion: usage of autologous platelet-rich plasma as a subconjunctival injection in treating corneal ulcers in dogs and cats is effective. The number of injections is the case and corneal ulcer type depended. Clinical significance: autologous platelet-rich-plasma as a subconjunctival injection in treating corneal ulcer is a relatively cheap, safe method and can be done in the clinical setting.